Effect of 2,4-D and Isoproturon on chromosomal disturbances during mitotic division in root tip cells of Triticum aestivum L. - Sanjay Kumar (Цитология и генетика, 2010)
In the present communication, author describes the effects of 2,4-D and Isoproturon on chromosomal morphology in mitotic cells of Triticum aestivum L.